LINGUISTICS AND ENGLISH LANGUAGE TEACHING - Effendy Gultom (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Linguistics is needed in English language teaching because it helps teachers explain the English components and structures to the students. Every language has a system or linguistic rules that can be learned in terms of phonology, morphology. syntax, and semantics. However, English language teaching should be incorporated with other fields sucl;as psychology, education- cognitive science, anthropology. language acquisition. sociology, bilingualism,and language teaching. Knowing the Students is very important for the teacher in order to create condusive classroom atmospheres. The teacher needs to have empathy and patience toward the students and he should be able to place himsellin the students' position. In general, the purpose of English teaching is to enable the students to use the language for communication fluently and appropriately both in oral and written forms. In order to achieve this purpose, the teacher must realize that the students are not blank spaces that can be filled with knowledge. The teacher can function as a coach, moderator, or adviser but he should give freedom to the students to experiment, ask questions, and express their ideas. Teaching English as a foreign language involves a lot of knowledge and strategies. An English teacher is expected to know the students and teaching objectives, the subject matter, some teaching methods, and broad general kno'"vledge. Furthermore, an English teacher must have strong motivation in doing his job in order to be a good model for the students.